A bidirectional authentication protocol for RFID based on Syn - Shanhua ZHAN; Shaorong HUANG (Dianxin kexue)
The RFID system is made up of three parts:tags,readers and databases.The information between tags and readers are transmitted through wireless channel,which is easy to be intercepted by attackers.A two-way authentication protocol based on word Synthesis operation was proposed.The two remainder theorem was used to encrypt communication messages by the proposed protocol,the difficulty of cracking was increased; In the process of each round of communication encryption,a random number was added to make the communication messages inconsistent,so that the tracking attacks could not be initiated by attackers.In the communication message encryption,the word synthesis algorithms was adopted at the same time,the total calculation of the system could be effectively reduced.A random checking mechanism was introduced at the database,enabling a synchronous attack and other attacks to be effectively resisted by the system.Security analysis shows that the protocol has high security,and performance analysis shows that the protocol has the standard of lightweight computation.